Value co-creation on repurchase intention in sharing economy platform - Hendar Hendar; Endang Dwi Astuti; Sri Hindah Pudjiastuti (Faculty of Economics and Business, University of Muhammadiyah Malang, 2022)
This study aims to empirically develop and evaluate the role of customer participation, customer ethical perception, and social support in creating value co-creation intention and repurchase intention for SEP customers in Indonesia. The theoretical model regarding the creation of value co-creation and repurchase intention is built based on a theory of planned behavior and literature on value co-creation, customer participation, marketing ethics, and social support. Therefore, using structural equation modeling, 376 empirical data for customers over 15 years old were analyzed. The results reveal that customer participation and ethical perception affect value co-creation intention, while social support does not. In addition, customer participation, ethical perception, SS, and value co-creation intention affect repurchase intention. Value co-creation intention becomes a partial mediator in the relationship between customer participation, customer ethical perception, and repurchase intention. Meanwhile, value co-creation intention cannot be a mediator in the relationship between social support and repurchase intention. This study contributes to the sharing economy literature by providing a holistic antecedent value co-creation intention model. Besides, it also offers important insights for SEP managers.